Modeling of a non-transferred arc plasma torch - Chinè-Polito, Bruno (2019)
Plasma torches are used in processing of materials and in energy industry for producing plasma, where direct currents arc torches represent the primary components of thermal plasma processes (plasma spraying, metal welding and cutting, waste treatment, biogas production, etc.). In a non-transferred arc plasma torch, an electric arc can be glowed by applying a direct current between the cathode and anode, both placed inside the torch. Then, the plasma is obtained by heating, ionizing and expanding a working gas, introduced into the chamber of the torch upstream of the cathode. Experimental works carried out by observation and measurements techniques are difficult to apply in this field, owing to the specific properties of these physical phenomena. Hence, computational techniques could represent a useful tool to investigate the plasma processing, although the computational work is extremely challenging, because the physical phenomena are not independent among them and simultaneous. In this work we provide a computational model for simulating a 2D non- transferred arc plasma torch, under hypothesis of local thermodynamic equilibrium. Steady state conditions are assumed for the equations of conservation of fluid mechanics, heat transfer and electromagnetics which are modeled by the Comsol Multiphysics® 5.1 software. The plasma is considered optically thin and a net emission coefficient is used for the heat transferred by radiation mechanisms. The gas flow is modeled as laminar with a free vortex at the inlet for two kinds of axisymmetric torches, one with argon and the second one with nitrogen as working gas, respectively.